Application of Reward and Punishment Methods to Increase Student Learning Motivation in PAI Subjects at SMKN 38 Jakarta Schools - Putri Aisyatun Najwa; Lismawati, Lismawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study has the aim of understanding the reward and punishment methodology in increasing student learning motivation in Islamic Religious Education (PAI) subjects at SMKN 38 Jakarta. The research method applied is qualitative with a case study approach. Data collection is carried out from observations, interviews, and documentation. Research acquisition to improve the implementation of reward and punishment effectively increase student learning motivation in PAI subjects. Rewards that are given in the form of praise, additional values, and prizes, and punishment in the form of reprimands, reduction of values, and additional tasks. The application of this method can encourage students to be more active, disciplined, and achievement in PAI learning. The implementation of this research is the importance of PAI teachers to apply the reward and punishment method wisely and in accordance with student needs to increase student motivation.